2012
DOI: 10.1158/1940-6207.capr-11-0442
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles Predict Early Nonadherence to Adjuvant Endocrine Treatment in a Prospective Breast Cancer Cohort

Abstract: Nonadherence to adjuvant endocrine breast cancer treatment adversely affects disease-free and overall survival. Clinical predictors of nonadherence may allow for specific interventions to reduce nonadherence and improve survival. The aim was to investigate whether clinical characteristics predict nonadherence. Clinical characteristics and information on adherence were obtained from 417 patients with breast cancer in a population-based prospective cohort from southern Sweden using patient charts, pathology repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…None of these potential confounders could explain the results of this study. A recent publication based on this cohort reported that poor adherence was associated with early events [45]. However, coffee intake was not associated with duration of endocrine therapy and could thus not explain the results.…”
Section: Discussionmentioning
confidence: 52%
“…None of these potential confounders could explain the results of this study. A recent publication based on this cohort reported that poor adherence was associated with early events [45]. However, coffee intake was not associated with duration of endocrine therapy and could thus not explain the results.…”
Section: Discussionmentioning
confidence: 52%
“…Previously, we have shown that overweight patients were more adherent to endocrine therapy; moreover, non-adherence was associated with a significantly increased risk of early breast cancer events [18]. In this study, the duration of endocrine treatment was not associated with the number of variant alleles of htSNPs1-4, number of htCCGC copies, or the presence of any htTCAC variant, indicating that adherence did not affect our findings.…”
Section: Discussioncontrasting
confidence: 41%
“…First, we might have missed additional patient related and psychological factors that might have found to be related to adherence in patients with other diseases 25. Second, we used non validated questionnaire to assess the factors influencing adherence except depression and third, it is possible that additional measures of adherence could have further contributed to a more sensitive definition of adherence in our study.…”
Section: Discussionmentioning
confidence: 99%